Upaya Pencegahan Dan Penangan Tindak Pidana Perdagangan Orang Berdasarkan UU 21 Tahun 2007 Tentang Perdagangan Orang - Intan Nurina Seftiniara; M.Cakra Bima; Dodi Setiawan (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Handling criminal acts of human trafficking in Indonesia, as mandated by Law Number 21 of 2007, involves aspects of protection and rehabilitation of victims. This article discusses the implementation of protection and rehabilitation in accordance with the mandate of the law, with a focus on the involvement of non-governmental organizations and international cooperation in increasing the effectiveness of these efforts. Addressing the complex nature of human trafficking requires collaboration across sectors and countries. The involvement of non-governmental organizations brings deep expertise and sensitivity, enriching protection and rehabilitation programs. In addition, international cooperation through organizations such as UNICEF and IOM broadens the reach of efforts and provides important global support. Obstacles such as cross-border complexity, limited resources, and lack of coordination between agencies are challenges, but corrective steps through harmonization of regulations, adequate budget allocation, and increased coordination can strengthen the law enforcement system. Developing community education, regular program evaluation, and sensitivity to cultural and gender aspects are also a focus in strengthening protection and rehabilitation. By identifying obstacles and taking appropriate corrective steps, efforts to deal with human trafficking crimes can become more holistic and effective.